2016
DOI: 10.1007/s11205-016-1292-7
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Occupational Mismatch: Overeducation and Overskill in Europe—Evidence from PIAAC

Abstract: Occupational mismatch has been a hot topic in the economics literature in recent decades; however, no consensus has been reached on how to conceptualise and measure this phenomenon. We explore the unique opportunity offered by the PIAAC survey to measure occupational mismatch at the individual level based on both education-(overeducation) and skill-based (overskilling) variables by using both objective and subjective measures. For this purpose, we use data on 17 European countries and compute up to 20 differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
99
2
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(128 citation statements)
references
References 43 publications
(55 reference statements)
5
99
2
11
Order By: Relevance
“…While an increasing number of universities have greater enrolment than in past decades, less attention is paid to their output quality in terms of balancing acquired skills with demanded skills. This has led to increasing the unemployment rate of graduated students, especially since the recession, as only a few graduated students possess required market skills [ [16]. For example, this mismatch contributed to approximately one-third of the recent rise in US unemployment [9], as the greater number of mismatches happen at the educational level.…”
Section: Fig 2: Dimensions Of Unemployment Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…While an increasing number of universities have greater enrolment than in past decades, less attention is paid to their output quality in terms of balancing acquired skills with demanded skills. This has led to increasing the unemployment rate of graduated students, especially since the recession, as only a few graduated students possess required market skills [ [16]. For example, this mismatch contributed to approximately one-third of the recent rise in US unemployment [9], as the greater number of mismatches happen at the educational level.…”
Section: Fig 2: Dimensions Of Unemployment Problemmentioning
confidence: 99%
“…In addition, one-ninth of the causes of unemployment during the great recession was due to skills mismatch in the Netherlands [15]. On the other hand, the study of [16] showed that a small rate of mismatch was related to both education and skills, while a larger rate was related to either education or skills only. In addition, it found that the relationship between education and skills mismatch was negative, which plays an important role in tackling this labor skills inefficiency.…”
Section: Fig 2: Dimensions Of Unemployment Problemmentioning
confidence: 99%
“…Because of improved data, it has become possible to differentiate between formal qualification mismatches and the mismatches between an individual's set of skills and the skills that are required for a certain job. Recent empirical studies conclude that formal qualification mismatch and skills mismatch are not necessarily the same phenomenon (Allen et al 2013;Allen/van der Velden 2001;Flisi et al 2016;McGowan/Andrews 2015). Employees can be formally well-matched but mismatched regarding skills (and vice versa).…”
Section: Introductionmentioning
confidence: 99%
“…Desjardins/Rubenson 2011;Flisi et al 2016;Levels et al 2014;McGowan/Andrews 2015;Pellizzari/Fichen 2013). Therefore, these studies can only focus on broad skill measures or general human capital.…”
Section: Introductionmentioning
confidence: 99%
“…Det kan også føre til mistilpasset sysselsetting sett i forhold til utdannelse, kvalifikasjoner og ferdigheter, samt i dårligere ansettelsesvilkår, se f.eks. Flisi, Goglio, Meroni, Rodrigues & Vera-Toscano (2017) og Montt (2017) om 'vertikal' og 'horisontal' mistilpasning. Denne artikkelen begrenser seg til mistilpasning som resulterer i manglende sysselsetting, noe som fører til både høyere samlet arbeidsledighet og større variasjon mellom ulike deler av arbeidsmarkedet, som regioner eller yrker.…”
unclassified